Penerapan Prinsip Desain Kengo Kuma Pada Women’s Opportunity Building Di Pekanbaru - Adip Padli; Yohannes Firzal; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Kengo Kuma was one of Japanese architects who based on design principles has always conscribed to human and natural interconnections to try a balance. Some of predominant characters of the Kuma are Transcendence, Passivity, Particilization , Temporality , and Subject- Object Relationship. Today one of the phenomena that still exixts is women’s chance inequality. Women’s opportunity building is a place in handling activities of coaching, empowerment and women’s protection. The concepts of the building is Hitoe (the name of the cherry blossoms which has five petals), selection of the concepts based on a Kuma’s who always inspired from nature. Data collection is collected from two sources, primary data (obsevation and documentation) and sekunder data (journal online, books, thesis, and media).Keywords: Hitoe , Kengo Kuma, Women’s Opportunity Building